2021
DOI: 10.3390/nano11030738
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial Strengthening of Graphene/Aluminum Composites through Point Defects: A First-Principles Study

Abstract: The relationship between point defects and mechanical properties has not been fully understood yet from a theoretical perspective. This study systematically investigated how the Stone–Wales (SW) defect, the single vacancy (SV), and the double vacancy (DV) affect the mechanical properties of graphene/aluminum composites. The interfacial bonding energies containing the SW and DV defects were about twice that of the pristine graphene. Surprisingly, the interfacial bonding energy of the composites with single vaca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 70 publications
0
7
0
1
Order By: Relevance
“…To explore the interaction between the defect and the surrounding atoms and to observe the charge redistribution and charge accumulation more intuitively, , we give the differential charge density diagrams of the three vacancy defects V Br , V Cs , and V Pd of Cs 2 PdBr 6 , as shown in Figure . It can be seen that the formation of the defect causes only slight charge fluctuations around it, and the formation of the V Br defect structure at its defect causes charge redistribution between the remaining Br atoms and the Pd atoms in the center of the octahedron, and the Br atoms undergo a charge exchange of gain and loss of electrons, but with the vacant Br atoms connected to the Pd atoms mainly exhibit electron loss.…”
Section: Resultsmentioning
confidence: 99%
“…To explore the interaction between the defect and the surrounding atoms and to observe the charge redistribution and charge accumulation more intuitively, , we give the differential charge density diagrams of the three vacancy defects V Br , V Cs , and V Pd of Cs 2 PdBr 6 , as shown in Figure . It can be seen that the formation of the defect causes only slight charge fluctuations around it, and the formation of the V Br defect structure at its defect causes charge redistribution between the remaining Br atoms and the Pd atoms in the center of the octahedron, and the Br atoms undergo a charge exchange of gain and loss of electrons, but with the vacant Br atoms connected to the Pd atoms mainly exhibit electron loss.…”
Section: Resultsmentioning
confidence: 99%
“…For practical applications in electronic devices, tailoring the electronic properties is highly desirable. Generally, defects and in-plane strains are inevitable during the experimental synthesis of 2D nanomaterials because of the influence of environmental conditions and substrate, which have a very significant effect on the structural and electronic properties of 2D nanomaterials [19][20][21][22][23][24][25][26]. For example, using first-principles calculations, Wei et al [21] explored the effect of vacancy defects on the electronic properties of the hexagonal BN monolayer and found that B_vacancy, N_vacancy, and double vacancy defects can induce direct to indirect band gap transition.…”
Section: Introductionmentioning
confidence: 99%
“…In a study by Wei et al 18 , they investigated the effect of vacancy defects on the electronic properties of the monolayer boron nitride and found that B-vacancy, N-vacancy, and double vacancy defects can eliminate bandgap from direct to indirect. Among various ways to modulate the electronic features of 2D systems, in general, defects and strains in the process of synthesis of 2D materials are ineluctable [18][19][20][21][22][23][24] , and effort to understand strain effects on the synthesized materials is very important in the nanoelectronic industry 25,26 .…”
Section: Introductionmentioning
confidence: 99%